2020
DOI: 10.21203/rs.3.rs-117309/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Clinical Features Between Patients with Positive and Negative Appendectomy

Abstract: Background: The objective of this study was to retrospectively compare clinical features and prognostic values between the patients who were referred to the general surgery clinic of our hospital with the presumed diagnosis of acute appendicitis and underwent positive or negative appendectomy.Methods: Patients were divided into two groups as positive (PA) (n:362) and negative appendectomy (NA) (n:284) and the data obtained were compared between these two groups.Laboratory investigations were performed in all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…4 In accordance with recent guidelines, the clinical diagnosis, imaging examinations, and certain biomarkers, such as white blood cell count (WBC) and Creactive protein (CRP) levels, are all required to assess the diagnosis of acute appendicitis. 5,6 There have been fewer cases of negative appendectomies as a result of recent developments in the imaging diagnosis and the early application of computed tomography (CT). 7,8 On other hand reported that, since more than twenty years ago, magnetic resonance imaging (MRI) has been utilized for the assessment of acute appendicitis.…”
Section: Introductionmentioning
confidence: 99%
“…4 In accordance with recent guidelines, the clinical diagnosis, imaging examinations, and certain biomarkers, such as white blood cell count (WBC) and Creactive protein (CRP) levels, are all required to assess the diagnosis of acute appendicitis. 5,6 There have been fewer cases of negative appendectomies as a result of recent developments in the imaging diagnosis and the early application of computed tomography (CT). 7,8 On other hand reported that, since more than twenty years ago, magnetic resonance imaging (MRI) has been utilized for the assessment of acute appendicitis.…”
Section: Introductionmentioning
confidence: 99%